In-Vitro Antioxidant Activity, Acute Oral Toxicity Studies and Preliminary Phytochemical Characterization of the Bark Extract of Terminalia arjuna (L.) - Samadhan G. Patil,; Bhushan S Bhadane,; Mohini P. Patil,; Sateesh Belemkar ,; Ravindra H. Patil, (Journal of Pharmacy and Nutrition Sciences, 2016)
The free radicals and the reactive oxygen species (ROS) are known to induce oxidative stress and it has been implicated in the pathology of cardiovascular diseases, inflammatory conditions, cancer and ageing. The activities associated with ROS can bedelayed, prevented or removedby antioxidant compounds (natural or synthetic). The use of synthetic antioxidants restricted because of their known side effects such as liver damage and carcinogenesis. The aim of this study to evaluate in vitro antioxidant and acute oral toxicity of Terminalia arjuna extracts. The present finding reveals that the purified fraction at100 µg/ml, showed maximum (91.32 ± 0.10 %,) DPPH radical scavenging effect in comparison with standard ascorbic acid (79.46 ± 0.10%) at the 10 µg/ml concentration. The reducing power of the purified extract was found to be dose dependent. Food and water intake of the animals in test and control groups was found normal during the 14 day acute oral toxicity studies and no apparent changes were observed in the internal organs of both, the test and control groups, after gross necropsy. The preliminary phytochemical screening of the crude acetone extract revealed dominant presence steroids, terpenoids, polyphenols, alkaloids and tannins. TLC profile of the purified fraction revealed a single band of Rf 0.38, a characteristic feature of triterpenoids. The UV absorption maximum of the purified fraction was recorded at 194nm. The FT-IR spectrum indicated presence of aromatic rings 3421 (COOH), 2957 (alkanes, CH2 and CH3), 1726 (carbonyl), 1599 (carboxylic acid), and region between 1000-1300 stretching of C-O, ester and ether carboxylic group. Thus, the isolated bioactive phytoconstituents form the bark extract of Terminalia arjuna could be used as natural anti-oxidants..